Prospective clinical trial of diagnostic peritoneal lavage to detect positive peritoneal cytology in patients with gastric cancer12. Issue 8 (26th March 2013) - Mezhir, James J.; Posner, Mitchell C.; Roggin, Kevin K.
Abstract Background and Objectives Positive peritoneal cytology equates M1 disease in patients with gastric cancer. Diagnostic peritoneal lavage (DPL) is a proven test to detect occult visceral injury in trauma patients. The objective of this study is to determine whether DPL can be used to assess peritoneal cytology in patients with gastric cancer. Methods Patients with gastric adenocarcinoma were prospectively enrolled to undergo DPL prior to diagnostic laparoscopy (DL). Saline was instilled through a percutaneous catheter and fluid was collected for cytology (DPL‐cyt). Washings obtained during DL were used as controls (DL‐cyt). Results DPL was successful in 22/27 patients (81.5%). Among the 22 successful DPLs, 12 had positive cytology (54.5%). Positive DPL‐cyt specimens matched DL‐cyt specimens in 12/12 cases (specificity = 100%). One of 10 cases with negative DPL‐cyt was positive on the final DL‐cyt (sensitivity = 92%). There were six patients with negative DPL‐cyt who had visible M1 disease diagnosed with DL (DPL evaluation of M1 disease, sensitivity 54.5%, specificity = 100%). Conclusions DPL is a safe method of detecting positive cytology in patients with gastric cancer, however gross M1 disease may be missed without visual inspection. The specific role of DPL in the staging workup of patients with gastric cancer remains to be determined. J. Surg. Oncol. 2013;107:794–798. © 2013 Wiley Periodicals, Inc.